Lameness in crossbred cows: Its effect on productive and reproductive performance - Tyagi, Kalpna (Indian Journal of Dairy Science, 2017)
Lameness is a common hoof disorder in dairy cows, significantly affects their productive and reproductive performances. Present study was conducted on 10 years (January, 2003 to December, 2012) lactation records of crossbred cows (n=1153). Overall lameness incidence in crossbred cows was 10.66% (123/1153). There was significant effect of parity on lameness (c2=17.9, df=4, P<0.001), where maximum incidence was observed in 1st parity (15.45%) cows. Lameness incidence was found to be highest in cows that calved in the year 2006 (15.00%) and lowest in the year 2009 (7.84%) but did not differ statistically (c2=9.2, df=9, P=0.419). Season wise lameness incidence was found significantly higher in winter calved cows than those calved in summer (14.37 vs. 6.49%, c2= 9.61, df=3, P=0.022). Lameness resulted significant (P<0.01) loss of milk (569.84 kg or 16.17%) in a period of 305 days than non-lame cow. In lame cows, service period (182.05 vs. 168.81 days), number of services per conception (2.07 vs. 1.94), calving to first service interval (108.23 vs. 101.33 days) and calving interval (449.66 vs. 441.31 days) were found higher than healthy cow, but did not differ statistically. Taken together, the present study concluded that lameness in crossbred cow reduced their both productive and reproductive performance.